Micropapillary bladder cancer: an added indication to prophylactic urethrectomy. Issue 11 (11th November 2021) - Mehrnoush, Vahid; Ismail, Asmaa; Zakaria, Ahmed; Elmansy, Hazem; Shahrour, Walid; Prowse, Owen; Kotb, Ahmed
Abstract: There is little research on the role of urethrectomy during cystectomy in patients with micropapillary bladder cancer (MPBC). We present two cases of MPBC cystectomy and suggest that urethrectomy be performed concurrently as a preventive measure. The first case involved a woman who had a mixed solid and papillary bladder tumour. An anterior pelvic exenteration was performed as well as a total urethrectomy. The T4a micropapillary variant tumour was confirmed by pathology. The second case involved a man with T1 MPBC who was treated with a BCG induction course. A recurrent muscle-invasive MPBC was discovered during follow-up. During the radical cystoprostatectomy, the urethra was spared. T2 MPBC was discovered through pathology. He had a urethrectomy 6 months later due to urethral bleeding, and the pathology revealed micropapillary cancer of the urethra.